Lietuviškoji mokslinė medicinos periodika Lietuvoje XX a. trečiajame-penktajame dešimtmetyje (iki 1994 m.) - Stakulienė, Silvija (Knygotyra, 2002)
The aim of this article - to overview two scientific medical periodical publications "Medicina" (Medicine) and "Vytauto Didžiojo universiteto Medicinos fakulteto darbai" (Scientific Works of the Medical Faculty of Vytautas Magnus). They were begun to be published in Lithuania only after having regained the freedom of the press. Research period covers the years 1920-1944. The author analyzes their origin, publishing process and consistency of evolution. It is still not well enough investigated subject in the history of Lithuanian medicine and press. The very first Lithuanian scientific magazine on medicine appearanced in 1913. It was „Medicina ir gamta" (Medicine and Nature) edited and issued by the famous doctor S. Matulaitis. Its publication was ceased and only after seven years, in 1920, there was issued the magazine "Medicina" (Medicine), the continuer of its ideas. The first editor of the aforementioned publication was J. Žemgulys. Since No 6/7 dated 1922, when he gave up his position as an editor the work was continued by J. Staugaitis. Medicina was published till 1944. Its contributors were famous physicians P. Avižonis, V. Lašas, V. Kuzma and others. After the joumal ceased being published, it was renewed only in 1990 under the same title. Since l 933, "Vytauto Didžiojo Universiteto Medicinos fakulteto darbai" (VDUMFD) started to be issued. It was an extremely significailt event in the history of Lithuanian medicine. This unique publication has been published during the years 1933-1942. lis first editor was professor P. Avižonis (1933-1939) who was active both in publishing and scientific work. After his death the position was taken over by professor V. Lašas ( 1939-1942). VDUMFD were published in non-periodical issues in 6-10 printer’s sheets. Three separate books or issuės comprised one volume. Many renowned scientisls collaborated in this publication: V. Kuzma, V. Mingailaitė-Tumėnienė, J. Žilinskas, K. Buinevičius and lots of unnamed; in all 34 physicians and 72 works from different subject areas were published. These first scientific medical publications Medicine and VDUMFD demonstrated that dedicated kernel of physicians has formed in Lithuania who were able to publish research works from their fields of interest. Due to their knowledge and experience, Lithuanian physicians were among the progressive ideas and scientific innovations propagating European representatives. These works were like the first beacons, which built a path into the future, directed to the new development trends in medicine and created preconditions for the establishment and development of famous Lithuanian medical institutions in Lithuania after the World War 11.